Developing the Physical Condition of Athletes Through the Prevention and Treatment of Sports Injuries - Dwi Darmawan, Agung; Kuntum Mandalawati, Titin; Ratna Kartini, Puri; Maritha, Vevi; T Candra, Arya (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
The prevention and treatment of injuries is a fundamental thing that every sports player must have, especially in developing physical condition, but what has happened to date is that prevention and initial treatment of sports injuries has not been carried out properly and correctly. Good physical condition can be achieved when an athlete has no complaints or injuries. Injuries can be treated by preventing and first treating sports injuries. Therefore, there is a need for dissemination regarding prevention, one of which is through socialization and mentoring. The results of the service in the form of socialization on the Development of Athletes' Physical Conditions Through the Prevention and Management of Sports Injuries got good results where 100% of the participants consisting of 1 coach and 27 athletes were very satisfied regarding the material presented, delivery of the material, discussions through question and answer sessions and mentoring at while practicing. The participants felt they had gained additional insight and skills in preventing and first treating sports injuries.